Sustainability design: Reduction of vehicle mass without compromizing crashworthiness - Tarlochan F.; Faridz A. (2023)
In former times, engineers were only concern about "designing" a product that meets its objectives. Little concern was given to the future availability of natural resources. Current design trends are more stringent to say. Not only the product has to fulfill its objectives/ functional performance, but it has to fulfill the market needs and at the same time ensuring there is minimal material or energy wastage. The objective of this study was to address the later requirement which is minimizing material wastage. The study focused on size optimization of the frontal vehicle structure via design of experiment and finite element analysis. The outcome of the study was encouraging. A weight savings of 8 kg was achieved without severely affecting the crashworthiness behavior of the vehicle. 2009 IEEE.